Functional Selectivity of Dopamine D1 Receptor Signaling: Retrospect and Prospect - Yang Yang (MDPI AG, 2021)
Research progress on dopamine D1 receptors indicates that signaling no longer is limited to G protein-dependent cyclic adenosine monophosphate phosphorylation but also includes G protein-independent β-arrestin-related mitogen-activated protein kinase activation, regulation of ion channels, phospholipase C activation, and possibly more. This review summarizes recent studies revealing the complexity of D1 signaling and its clinical implications, and suggests functional selectivity as a promising strategy for drug discovery to magnify the merit of D1 signaling. Functional selectivity/biased receptor signaling has become a major research front because of its potential to improve therapeutics through precise targeting. Retrospective pharmacological review indicated that many D1 ligands have some degree of mild functional selectivity, and novel compounds with extreme bias at D1 signaling were reported recently. Behavioral and neurophysiological studies inspired new methods to investigate functional selectivity and gave insight into the biased signaling of several drugs. Results from recent clinical trials also supported D1 functional selectivity signaling as a promising strategy for discovery and development of better therapeutics.